Power generation employing a thermoelectric generator - Ginju Rose George (2014)
Thermoelectric modules can be used to convert heat energy to electricity. The science of thermoelectricity originated in 1800s when Estonian born German physicist Thomas Seebeck discovered that a junction of dissimilar metals produces a current when exposed to a temperature gradient. The technology gained significant interest in recent years due to technological advancements in the semiconductor industry and the need to find renewable sources of energy. Thermoelectric generators are all solid–state devices and unlike traditional dynamic heat engines, they contain no moving parts and are completely silent. Due to the low electric power output over heat input, thermoelectric generators are not commercially viable. In the search for better thermoelectric materials, a clearer understanding of the impact of the various effects on the amount of heat input and electrical power output has to be established. In this project, the performance of a thermoelectric module was analysed experimentally. The experimental set-up consists of a commercially available Bismuth telluride thermoelectric module with varying heat inputs placed in a vacuum chamber. A set of equations were proposed that provides considerations for Fourier’s law and the Seebeck and Peltier effects. The performance of the thermoelectric generator was verified using the data obtained previously with the same rig. The results showed similar trends to previous data but yield lower efficiency. The discrepancy was found to be due to the lower Seebeck coefficient of the new thermoelectric element. The thermoelectric module analysed in this experiment produced a maximum efficiency of 2.45%. The results show that a heat source that is isolated and placed in vacuum condition presents a much higher performance than many other researches.